Orthodontics and Endodontics: clinical decision-making - Consolaro,Alberto (2020)
ABSTRACT Endodontically treated teeth may be moved, as endodontic treatment is not a contraindication for orthodontic treatment. Apical periodontal repair begins when the periapical or pulp lesion has completely resolved. This may happen immediately after treatment if the filling material causes little or no irritation of periapical tissues, and particularly if the material is fully contained within the canal. When it leaks, a foreign body granuloma forms and persists for some months or indefinitely, depending on the composition of the filling material. Materials containing calcium hydroxide with no resin components undergo phagocytosis and disappear in some months, as macrophages gradually remove them. Materials containing resins, silicone, ionomers, zinc oxide-eugenol, bioceramics or gutta-percha remain in the site and induce the formation of foreign body granulomas. Although this does not preclude tooth movement, patients should be followed up every three months using periapical images to control the position of the material in relation to the tooth apex. “Pseudo” overfilling may be avoided if permanent filling is delayed until the time when orthodontic treatment is completed.